Characterization of snakehead (Channa argus) interleukin-21: Involvement in immune defense against two pathogenic bacteria, in leukocyte proliferation, and in activation of JAK–STAT signaling pathway. Issue 123 (April 2022) - Li, Dongqi; Cui, Zhengwei; Zhao, Fei; Zhu, Xueqing; Tan, Aiping; Deng, Yuting; Lai, Yingtiao; Huang, Zhibin
Abstract: Interleukin-21 (IL-21), a crucial immune regulatory molecule, belongs to the common γ-chain family of type I cytokines, and exerts pleiotropic effects on multiple immune cell types in mammals. However, the characteristics and functions of fish IL-21 remain unclear. To further investigate the molecular mechanism of IL-21 in teleosts, we first cloned and identified the IL-21 gene (designated shIL-21 ) of the snakehead ( Channa argus ). The full-length open reading frame of shIL-21 is 438 bp in length, and encodes a predicted protein of 145 amino acid residues. A sequence analysis showed that shIL-21 has the typical structural characteristics of other IL-21 proteins, containing four α-helices and four conserved cysteine residues. In a phylogenetic analysis, shIL-21 clustered within a subgroup of IL-21 proteins from other teleost species and shared its closest evolutionary relationship with that of Lates calcarifer . The expression analysis showed that shIL-21 was ubiquitously expressed in all the healthy snakehead tissues tested, albeit at different levels. After infection with Nocardia seriolae or Aeromonas schubertii, the relative expression of shIL-21 was mainly upregulated in the head kidney and spleen in vivo . Similarly, after stimulation with the three pathogen analogues lipoteichoic acid, lipopolysaccharides, and polyinosinic–polycytidylic acid, the expression of shIL-21 was also induced in head kidney leukocytes in vitro . A recombinant shIL-21 protein was expressed and purified, and promoted the proliferation of head kidney leukocytes, induced the expression of genes encoding critical signaling molecules in the Janus kinase (JAK) and signal transducer and activator of transcription (STAT) pathway, including JAK1, JAK3, STAT1, and STAT3, and induced the expression of endogenous shIL-21 and genes encoding several key proinflammatory cytokines (tumor necrosis factor-α, interferon-γ, and IL-1β ). Taken together, these preliminary findings suggest that shIL-21 is involved in the immune defense against bacterial infection, in leukocyte proliferation, and in the activation of the JAK–STAT pathway. They thus extend the functional studies of IL-21 in teleosts. Highlights: Snakehead IL-21 (shIL-21) was identified and characterized. ShIL-21 was induced by infection with two pathogenic bacteria in vivo. ShIL-21 was induced by stimulation with LTA, LPS, and poly(I:C) in vitro. Recombinant shIL-21 promoted the leukocyte proliferation. Recombinant shIL-21 induced the expression of genes in JAK–STAT pathway.